Progress of RAGE Molecular Imaging in Alzheimer’s Disease - Kong, Yanyan; Liu, Cuiping; Zhou, Yinping; Qi, Jingxuan; Zhang, Chencheng; Sun, Bomin; Wang, Jiao; Guan, Yihui (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by senile plaques (SPs), which are caused by amyloid beta (Aβ) deposition and neurofibrillary tangles (NFTs) of abnormal hyperphosphorylated tau protein. The receptor for advanced glycation end products (RAGE) binds to advanced glycation end products deposited during vascular dysfunction. Alzheimer’s disease may occur when RAGE binds to Aβ and releases reactive oxygen species, further exacerbating Aβ deposition and eventually leading to SPs and NFTs. As it is involved in early AD, RAGE may be considered as a more potent biomarker than Aβ. Positron emission tomography provides valuable information regarding the underlying pathological processes of AD many years before the appearance of clinical symptoms. Thus, to further reveal the role of RAGE in AD pathology and for early diagnosis of AD, a tracer that targets RAGE is needed. In this review, we first describe the early diagnosis of AD and then summarize the interaction between RAGE and Aβ and Tau that is required to induce AD pathology, and finally focus on RAGE-targeting probes, highlighting the potential of RAGE to be used as an effective target. The development of RAGE probes is expected to aid in AD diagnosis and treatment.